"Un abrazo a la distancia": An Exploration of Spanish-Speaking Women's Experiences with Pregnancy and Social Isolation in an Urban U.S. Setting. (June 2022) - Robledo-Gil, Talia; Kemet, Shakkaura; Pensak, Meredith; Cutler, Abigail; McNamara, Blair; Kennedy, Holly Powell; Lundsberg, Lisbet; Gariepy, Aileen
Introduction: Research on Spanish-speaking Latina/Hispanic women's experiences during pregnancy is limited.Methods: We recruited women from urban, walk-in pregnancy testing clinics from June 2014 to June 2015. Women aged 16–44 years, at less than 24 weeks gestational age, who spoke either English or Spanish were eligible and completed an enrollment questionnaire and individual interview according to language preference. During qualitative interviews, we explored pregnancy intentions, initial reactions to a new pregnancy, and feelings about the impact of this pregnancy on relationships and daily life. Qualitative narrative content analysis was conducted using Atlas.ti software.Results: Among interviews with 31 Spanish-speaking Latina/Hispanic pregnant women, participants' average age was 28 years old with a mean gestational age of 7 weeks. We identified social isolation as the most common theme, characterized by four interwoven and overlapping subthemes: (1) sola—the experience of feeling alone; (2) familismo cercano—the importance of close relationships; (3) familismo lejano—overcoming long distance relationships; and (4) mi patria—preserving homeland cultural connectedness.Conclusions: Spanish-speaking Latina/Hispanic pregnant women described experiencing multiple aspects of social isolation. Language preference may suggest risk of social isolation, necessitating provider awareness and support initiatives to improve social support and lessen social isolation among newly pregnant, Spanish-speaking Latina women.